Role of Flt-3 Growth Factor in Regulation of AC133+ Cells of Cord Blood Proliferative Activity - Bilko, N. M.; Vasilovskaya, S. V.; Bilko, D. I.; Votyakova, I. A. (Problems of Cryobiology and Cryomedicine, 2008)
AC133+ fraction of the cord blood cells separated by magnetic bead sorting was incubated with (10 ng/ml) during 12–18 hours that induced statistically significant enrichment of the colony formation in vitro of functionally active hematopoietic progenitor cells.